Предмет: Математика, автор: bodyabozhuk

Пж Помогите
Дам 50 баллов​

Приложения:

Ответы

Автор ответа: iramazurk
0

Пошаговое объяснение:

1

5 - (n + 5) = 5 - n - 5 = -n (Б)

2

-(n - 4) + (-3) = -n + 4 - 3 = -n + 1 (Г)

3

2 - (2 - n) = 2 - 2 + n = n (A)

4

-(-n + 2) + 1 = n - 2 + 1 = n - 1 (B)

Автор ответа: сок111213
0

1) Б

5 - (n + 5) = 5 - n - 5 =  - n

2) Г

 - (n - 4) + ( - 3) =  - n + 4 - 3 =  - n + 1

3) А

2 - (2 - n) = 2 - 2 + n = n

4) В

 - ( - n + 2) + 1 = n - 2 + 1 = n - 1

Похожие вопросы